2013
DOI: 10.1007/978-3-319-00200-2_2
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Branch-and-Cut Algorithms for the Equicut Problem

Abstract: A minimum equicut of an edge-weighted graph is a partition of the nodes of the graph into two sets of equal size such that the sum of the weights of edges joining nodes in different partitions is minimum. We compare basic linear and semidefinite relaxations for the equicut problem, and find that linear bounds are competitive with the corresponding semidefinite ones but can be computed much faster. Motivated by an application of equicut in theoretical physics, we revisit an approach by Brunetta et al. and prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…Buchheim et al (2008) make the separation problem for target cuts tractable by considering a sufficiently small projection of the polytope. Target cuts in this form have been computationally investigated for a number of applications: certain constrained quadratic 0-1 problems (Buchheim et al 2010), the maximum cut problem (Bonato et al 2014), the equicut problem (Anjos et al 2013), and robust network design (Buchheim et al 2011). Our method differs from their approach in that we turn the cut generation tractable by using relaxed decision diagrams instead of projection.…”
Section: Target Cutsmentioning
confidence: 99%
“…Buchheim et al (2008) make the separation problem for target cuts tractable by considering a sufficiently small projection of the polytope. Target cuts in this form have been computationally investigated for a number of applications: certain constrained quadratic 0-1 problems (Buchheim et al 2010), the maximum cut problem (Bonato et al 2014), the equicut problem (Anjos et al 2013), and robust network design (Buchheim et al 2011). Our method differs from their approach in that we turn the cut generation tractable by using relaxed decision diagrams instead of projection.…”
Section: Target Cutsmentioning
confidence: 99%
“…The NP-complete problems implementable in this way include the number-partitioning problem, the integer knapsack problem [16], and the Coulomb glass problem, which-as shown in Anjos et al [49]-can be mapped to a class of opti-cut problems. We summarize the description of the necessary Hamiltonian parameters in Table 1.…”
Section: Np-complete Models Realizable With Available Trapped-ion Tecmentioning
confidence: 99%
“…Alternatively, this latter constraint added to the max-cut problem gives the equicut problem which can be motivated by an application to Coulomb glasses in theoretical physics. Motivated by this application, Anjos et al [5] recently proposed an enhanced branch-and-cut algorithm for equicut based on an approach proposed by Brunetta et al [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Anjos et al [5] compared basic LP and SDP relaxations for the equicut problem, and found that linear bounds can be competitive with the semidefinite ones and can be computed much faster. While their results appear to contradict the above observations, it is important to note that they focus on dense instances coming from the physics application, and that their specialized relaxation includes constraints that are not valid for the minimum bisection polytope in general.…”
Section: Introductionmentioning
confidence: 99%